Screening of barley germplasm and released cultivars against stripe disease (Drechslera graminea) under artifical inoculation condition - Kumar, Virendra; Shekhawat, P. S.; Kanwar, Harshraj (Journal of Cereal Research, 2019)
Barley (Hordeum vulgare L.) is the fourth largest cereal crop in the world with a share of 7% of the global cereal production (Pal et al., 2012). It is mainly grown as a rabi season crop in different temperate regions of the world including India. Barley is used as a feed for animals, malt for industrial uses and for human food. At present, Barley is subjected to various fungal, bacterial, viral and noninfectious diseases. The major barley diseases prevalent in the world as well as in India include leaf rust, covered and loose smut, spot or net blotch, powdery mildew, stripe disease, bacterial blight and molya. Stripe disease caused by Drechslera graminea (Telomorph: Pyrenophora graminea) is an important seed borne disease of barley and responsible for 21.6% - 31.9% yield losses in Rajasthan.